Development of Critical Infrastructure Resilienceby Using Virtual Failure Simulations on the Exampleof a Power Plant - Andrzej GRABOWSKI (Zwiększanie odporności infrastruktury krytycznej poprzez wykorzystanie wirtualnych symulacji awarii na przykładzie elektrowni, 2022)
Resilience of Critical Infrastructure (CI) facilities defined as a capacity for further operation even upon changes that may result from natural or human-made disasters is extremely important from the perspective of functioning of society. Resilience of critical infrastructure facilities may be developed by taking such activities as introducing changes to their structure based on results of simulations of functioning of CI facilities. Another solution is to make use of computer simulations for better preparation of persons responsible for the functioning of CI facilities. This article describes a reference CI facility with potential scenarios of development of emergency situations and with a set of optional courses of an emergency situation. The scenarios were used to prepare a training application based on virtual reality techniques with an interface allowing a wide spectrum of interactions with a virtual environment, including commands issued to other employees, to be executed.
Keywords: Zwiększanie odporności infrastruktury krytycznej